Antidepressant pharmacological mechanisms: focusing on the regulation of autophagy - Lv, Shimeng; Zhang, Guangheng; Huang, Yufei; Li, Jiamin; Yang, Ni; Lu, Yitong; Ma, Haoteng; Ma, Yuexiang; Teng, Jing (Frontiers in Pharmacology, 2023)
The core symptoms of depression are anhedonia and persistent hopelessness. Selective serotonin reuptake inhibitors (SSRIs) and their related medications are commonly used for clinical treatment, despite their significant adverse effects. Traditional Chinese medicine (TCM), with its multiple targets, channels, and compounds, exhibit immense potential in treating depression. Autophagy, a vital process in depression pathology, has emerged as a promising target for intervention. This review summarized the pharmacological mechanisms of antidepressants by regulating autophagy. We presented insights from recent studies, discussed current research limitations, and proposed new strategies for basic research and their clinical application in depression.